PENGARUH REVOLUSI DIGITAL TERHADAP PROGRAM PEMASARAN - Agus Hasan Pura A (Bina Ekonomi, 2006)
The digital revolution of the marketplace allows much greater customization of products, services, and promotional messages than older marketing tools. By doing so, it enables marketers to build and maintain relationship with customers but on much greater and more efficient scale.